2017
DOI: 10.1038/s41598-017-11914-6
|View full text |Cite
|
Sign up to set email alerts
|

Semaphorin 3 C drives epithelial-to-mesenchymal transition, invasiveness, and stem-like characteristics in prostate cells

Abstract: Prostate cancer (PCa) is among the most commonly-occurring cancers worldwide and a leader in cancer-related deaths. Local non-invasive PCa is highly treatable but limited treatment options exist for those with locally-advanced and metastatic forms of the disease underscoring the need to identify mechanisms mediating PCa progression. The semaphorins are a large grouping of membrane-associated or secreted signalling proteins whose normal roles reside in embryogenesis and neuronal development. In this context, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 63 publications
(57 reference statements)
3
24
0
Order By: Relevance
“…Recent studies have shown that SEMA3C plays an oncogenic role and associated with poor prognosis and progression in multiple cancer types, including breast cancer [12,13,24]. Moreover, SEMA3C has been demonstrated to play a key role in maintaining stemcell-like cell features in glioblastoma and prostate cancer [13,33,45,46]. However, our study showed that altered expression of SEMA3C associated with poor prognosis in THCA, KIRC, KIRP, HNSC, PAAD, LUAD and CESA, but also associated with survival advantage in UVM, MESO, and DLBC which is all cell context dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that SEMA3C plays an oncogenic role and associated with poor prognosis and progression in multiple cancer types, including breast cancer [12,13,24]. Moreover, SEMA3C has been demonstrated to play a key role in maintaining stemcell-like cell features in glioblastoma and prostate cancer [13,33,45,46]. However, our study showed that altered expression of SEMA3C associated with poor prognosis in THCA, KIRC, KIRP, HNSC, PAAD, LUAD and CESA, but also associated with survival advantage in UVM, MESO, and DLBC which is all cell context dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression of SEMA3C is associated with poor prognosis and tumor progression in a number of cancers (Yamada et al , ; Martin‐Satue & Blanco, ; Konno, ; Galani et al , ; Herman & Meadows, ; Miyato et al , ; Xu et al , ). In PCa, SEMA3C promotes cell migration and invasion in vitro (Herman & Meadows, ) and drives EMT and stemness (Tam et al , ) and SEMA3C expression is a predictive marker for biochemical recurrence (BCR) (Li et al , ). Therefore, we investigated whether SEMA3C could be a key growth factor that drives CRPC progression and treatment resistance, and set out to develop a therapeutic protein inhibitor of SEMA3C signaling.…”
Section: Introductionmentioning
confidence: 99%
“…A axon guidance signaling molecules have previously been are implicated in the progression of EMT during tumor metastasis. 24-26 Actin cytoskeleton, Interleukin, ephrin receptor signaling pathways were also enriched. Based on IPA and GSEA findings indicating very significant altered expression of axon guidance-related genes, we analyzed RNA-Seq data for coordination of major guidance cue ligand/receptor pairings, such as 1) semaphorins, which bind with plexins/neuropilins receptors, 2) netrins, which bind with DCC (Deleted in Colorectal Cancer)/UNC5 (Un-Coordinate loss-of-function) receptors, 3) slits, which bind with ROBO (Roundabout) receptors, and 4) ephrins, which bind with Eph receptors.…”
Section: Resultsmentioning
confidence: 99%